1995
DOI: 10.1007/bf00003550
|View full text |Cite
|
Sign up to set email alerts
|

Immunological detection of the fungal parasite, Pythium sp.; the causative organism of red rot disease in Porphyra yezoensis

Abstract: The red rot disease of Porphyra yezoensis Ueda (Rhodophyta) is caused by a parasitic fungus, Pythium sp. To facilitate the detection of this pathogen in infected thalli of P. yezoensis, polyclonal and monoclonal antibodies were prepared. Antibodies were raised against antigen prepared from an isolate of fungal hyphae obtained from red-rot infected thallus of P. yezoensis from Aichi Prefecture. Polyclonal antibody was obtained from the antisera of immunized rabbits. Monoclonal antibody was obtained from the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In both Korea and Japan, immersion of cultivation nets into an organic acid-seawater mixture is already used to control disease by Pyropia farmers (Amano et al 1995;Park et al 2006). Sakaguchi et al (2001) reported that thalli were acid Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In both Korea and Japan, immersion of cultivation nets into an organic acid-seawater mixture is already used to control disease by Pyropia farmers (Amano et al 1995;Park et al 2006). Sakaguchi et al (2001) reported that thalli were acid Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Red rot disease (Akagusare), caused by Pythium porphyrae (Oomycetes), is one of the most destructive fungal diseases of Porphyra and can seriously reduce both yield and quality in Porphyra farms every year (Amano et al, 1995). The causative organism of this disease is spread by zoospores released into seawater.…”
Section: Introductionmentioning
confidence: 99%
“…To find red rot disease in the early stage, polyclonal antibodies (Pabs) (Addepalli & Fujita, 2001), monoclonal antibodies (MAbs) (Amano et al, 1995;Addepalli & Fujita, 2002b) and PCR technique (Park et al, 2001) have been developed. These researches have a great help to forecast the outbreak of red rot disease.…”
Section: Introductionmentioning
confidence: 99%